Review of the AC Overhead Wires, the DC Third Rail and the DC Fourth Rail Transit Lines: Issues and Challenges - Rahman F.A.A.; Kadir M.Z.A.A.; Osman M.; Amirulddin U.A.U. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric current collection; Overhead lines; Rapid transit; Bus Rapid Transit; Issues and challenges; Light rail transit (LRT); Overhead wires; Rail transit lines; Statistical datas; Transit systems; Voltage supply; Light rail transit